FRI0105 Benefit of Biologic Initiation in Moderate VS Severe Rheumatoid Arthritis: Evidence from a Real-World Registry. (9th June 2015) - Kavanaugh, A.; Greenberg, J.; Reed, G.; Griffith, J.; Friedman, A.; Saunders, K.; Ganguli, A.
Abstract : Background: Current treatment recommendations recommend accelerating therapy when rheumatoid arthritis (RA) patients (pts) reach moderate to severe disease activity. Objectives: To assess whether initiating biologics among pts with moderate RA results in better clinical outcomes compared with pts with severe RA. Methods: Data (10/2001–03/2013) were from the Corrona RA registry. The study population included RA pts who initiated a biologic for the first time and had 1 and 2 years (yrs) of follow-up and a Clinical Disease Activity Index (CDAI) score >10 at the time of biologic initiation. For analysis, pts were divided into 2 groups: those with moderate disease activity (10 < CDAI ≤22) and those with severe disease activity (CDAI>22). Clinical outcomes were percent of pts in remission (CDAI≤2.8), percent of pts with low disease activity (CDAI≤10), mean change in CDAI and modified HAQ (mHAQ), and mean cumulative CDAI and mHAQ (area under the curve standardized by length of follow-up computed for each pt). Outcomes were compared using Mann-Whitney-Wilcoxon rank tests and Fisher's exact test. A mixed-effects linear regression model was used to estimate mean CDAI and mHAQ over time for both groups. Results: 1596 (moderate:779;severe:817) and 1269 (moderate:634;severe:635) RA pts with 1 and 2 yrs of follow-up, respectively, were identified. Baseline characteristics (eg. age, sex, duration of RA, yr of initiation) for the 1-yr cohort were similar between moderate and severe disease activity initiators except for measures related to disease activity: median CDAI (16.1 vs 31.1), mHAQ (0.30 vs 0.60), tender joint count (4.0 vs 11.0), and swollen joint count (5.0 vs. 11.0); all P<.0001. At 1 yr after initiation of biologics, remission rates in pts with moderate and severe disease were 22.7% and 15.8%, respectively and rates of low disease activity were 60.1% and 41.2%, respectively, both P<.0001. At 1 yr, mean change (moderate vs severe, all P<.0001) in CDAI and mHAQ were -6.0 vs -18.9 and -0.1 vs -0.2, respectively; mean cumulative CDAI and mHAQ were 11.7 vs 20.4 and 0.36 vs 0.52, respectively. The model-based analysis revealed that moderate disease activity initiators achieved significantly lower CDAI and mHAQ scores (9.9 and 0.32 at 6 months) compared with severe disease activity initiators (5.3 and 0.46 at 6 months); these improvements were sustained in both groups (Figures 1 & 2 ). Results were similar for the 2-yr cohort. Conclusions: This real-world analysis showed that pts with moderate disease activity who initiate treatment with biologics achieve lower levels of disease activity significantly more than those with severe disease. This information will be helpful to clinicians in a T2T setting where achieving a target is the desired outcome. Acknowledgements: The Corrona LLC RA registry has been supported through contracted subscriptions in the last 2 yrs by AbbVie, Amgen, AstraZeneca, Genentech, Horizon Pharma, Lilly, Novartis, Pfizer and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Joann Hettasch PhD of Arbor Communications Inc provided medical writing and editing services in the development of this abstract. Financial support for these services was provided by AbbVie. Disclosure of Interest: A. Kavanaugh Grant/research support from: AbbVie, Amgen, Janssen, L.P., UCB, J. Greenberg Shareholder of: Corrona, LLC., Consultant for: Astra Zeneca, Celgene, Pfizer, Novartis, Employee of: Corrona, LLC., G. Reed Employee of: Corrona, LLC., J. Griffith Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., A. Friedman Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc., K. Saunders Employee of: Corrona, LLC., A. Ganguli Shareholder of: AbbVie, Inc., Employee of: AbbVie, Inc.